Enhancing Scientific Literacy on Global Warming in Junior High School: The Role of SETS-Oriented Guided Inquiry and Infographic-Based Multimedia - Azhar; Hasan Subekti (Science Education and Application Journal, 2026)
Scientific literacy in the context of global warming remains a persistent challenge in science learning, particularly in students’ ability to interpret data and use evidence for decision-making in real-world contexts. This study aimed to examine the effect of a SETS (Science, Environment, Technology, and Society)-oriented Guided Inquiry Learning model supported by infographic-based multimedia on students’ scientific literacy. The research was conducted at SMP Negeri 52 Surabaya with 30 seventh-grade students during the 2025/2026 academic year on the topic of global warming. A pre-experimental one-group pretest–posttest design was employed to investigate changes in students’ scientific literacy before and after the implementation of the learning model. The intervention was carried out over four weeks in eight instructional sessions. Data were collected through validated multiple-choice and essay-based pretests and posttests and were analyzed using N-Gain and paired-samples t-test. The results indicated a statistically significant improvement in students’ scientific literacy (p < .05) with an average N-gain of 0.53 (medium category). These findings suggest that integrating SETS-oriented guided inquiry learning with infographic-based multimedia can enhance students’ engagement and support the development of scientific literacy, particularly in understanding complex environmental issues such as global warming.